Text, thought, and practice in Qumran and early Christianity : proceedings of the Ninth International Symposium of the Orion Center for the Study of the Dead Sea Scrolls and Associated Literature, jointly sponsored by the Hebrew University Center for the Study of Christianity, 11-13 January, 2004 - Clements, Ruth.; Schwartz, Daniel R. (Studies on the Texts of the Desert of Judah, 2009)
The 13 papers comprising this volume represent the fruits of the first Orion Center Symposium devoted to the comparison of the Dead Sea and early Christian texts. The authors reject the older paradigm which configured the similarities between Qumran and early Christian literature as evidence of "influence" from one upon the other. They raise fresh methodological possibilities by asking how insights from each of these two corpora illuminate the other, and by considering them as parallel evidence for broader currents of Second Temple Judaism. Topics addressed include specific exegetical and legal comparisons; prophecy, demonology, and messianism; the development of canon and the rise of commentary; and possible connections between the Gospel of John and the Dead Sea Scrolls.